Stepwise Encapsulation of Sulfate Ions by Ferrocenyl‐Functionalized Tripodal Hexaurea Receptors. Issue 27 (15th May 2013) - Huang, Xiaojuan; Wu, Biao; Jia, Chuandong; Hay, Benjamin P.; Li, Minrui; Yang, Xiao‐Juan
Abstract Three ferrocenyl‐functionalized tripodal hexaurea anion receptors with ortho‐ (L2), meta‐ (L3), and para‐phenylene (L4) bridges, which showed strong binding affinities toward sulfate ions, have been designed and synthesized. In particular, meta‐phenylene‐bridged ligand L3, owing to its trigonal bipyramidal structure, can encapsulate two SO42− ions in its "inner" and "outer" tripodal clefts, respectively, as supported by their clearly distinct NMR resonances and by molecular modeling. The sulfate complex of ortho‐ligand L2, (TBA)2[SO4⊂L2]⋅2 H2O (1), displays a caged tetrahedral structure with an encapsulated sulfate ion that is hydrogen bonded by the six urea groups of ligand L2. CV studies showed two types of electrochemical response of the ferrocene/ferrocenium redox couple upon anion binding, that is, a shift of the wave and the appearance of a new peak. Quantitative binding data were obtained from the NMR and CV titrations.